2000
DOI: 10.1002/1097-0215(20001020)90:5<256::aid-ijc2>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline improves the oxygenation and radiation response of BA1112 rat rhabdomyosarcomas and EMT6 mouse mammary carcinomas

Abstract: Tumor hypoxia can significantly impact the efficacy of cancer therapy. Pentoxifylline, a methylxanthine derivative, can improve oxygen delivery to tissues and is widely used in the treatment of peripheral vascular disease and various cerebrovascular disorders. In this article, we show that pentoxifylline, combined with oxygen breathing, significantly improves the radiation response of two experimental tumors in vivo through improved tumor oxygenation. We also demonstrate that pentoxifylline does not directly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The BA1112 tumor has been used extensively in radiation biology and experimental cancer therapy studies in our laboratory and elsewhere. 3538 The BMB subline arose as a spontaneous variant of the BA1112, and was first noted during a tumor therapy experiment, when rats bearing the normally non-metastatic BA1112 tumors began developing large numbers of lung metastases while being followed for long-term tumor control (cure). The growth rate and histology of this metastatic subline resemble those described previously for the parental tumor line; 35,38 however, the incidence of lung metastases is greatly elevated.…”
Section: Methodsmentioning
confidence: 99%
“…The BA1112 tumor has been used extensively in radiation biology and experimental cancer therapy studies in our laboratory and elsewhere. 3538 The BMB subline arose as a spontaneous variant of the BA1112, and was first noted during a tumor therapy experiment, when rats bearing the normally non-metastatic BA1112 tumors began developing large numbers of lung metastases while being followed for long-term tumor control (cure). The growth rate and histology of this metastatic subline resemble those described previously for the parental tumor line; 35,38 however, the incidence of lung metastases is greatly elevated.…”
Section: Methodsmentioning
confidence: 99%
“…Investigators believe that MWCNTs-collagen scaffolds signifi cantly enhanced the differentiation of MSCs at 10 ppm. In another study, investigators showed that all types of MWCNT-collagen scaffolds induced the higher level of MSC differentiation compared to controls [60]. However, MWCNTs-collagen scaffolds were less likely to affect MSCs proliferation with no signifi cant difference in MSC morphology before and after differentiation.…”
Section: Characterization and Toxicity Of Swcnt And Mwcnt Carbon Nano...mentioning
confidence: 96%
“…The MRI microimaging was performed before and after placing nm CNT in glass capillaries at different intervals of 2, 4, 6 hours using scan parameters: TR/TE/fl ip angle = 750ms/ 4.18ms/25°, FOV/matrix size/spatial resolution = 2.6×3.4 cm/ 256×256/0.015 mm, and the inversion time (TI approximately 250 ms) set to null normal skin. Epidermis and hair follicle were measured as reported by Sharma et al (2010) [60].…”
Section: Characterization and Toxicity Of Swcnt And Mwcnt Carbon Nano...mentioning
confidence: 99%
“…90 A number of other agents evaluated preclinically, including pentoxifylline and nicotinamide, also improved tumor blood flow and response to radiotherapy. [91][92][93] However, clinical trials of nicotinamide have encountered considerable toxicities, with some patients experiencing nausea and vomiting that was unresponsive to antiemetics. 91 high oxygen content breathing Hyperbaric chambers Oxygen delivery to tissues is dependent on several factors, mainly blood flow, oxygen content, and oxygen tension.…”
Section: Overcoming Anemiamentioning
confidence: 99%